2012
DOI: 10.1089/apc.2011.0371
|View full text |Cite
|
Sign up to set email alerts
|

Using Laboratory Surveillance Data to Estimate Engagement in Care Among Persons Living with HIV in Los Angeles County, 2009

Abstract: Poor engagement in HIV care has been associated with delayed access to antiretroviral treatment and increased HIV transmission. Using viral load (VL) results from HIV laboratory surveillance data to conduct longitudinal and cross-sectional analyses, we examined linkage to care, retention in care, and their associated factors in 37,325 persons living with HIV (PLWH) in Los Angeles County (LAC). Linkage to care was considered timely if a VL test result was present ≤3 months of diagnosis. Successful retention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…Similar to previous studies, we found that regardless of care-seeking behaviors, women who are out of care were more likely to be uninsured. 14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Similar to previous studies, we found that regardless of care-seeking behaviors, women who are out of care were more likely to be uninsured. 14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors.…”
Section: Discussioncontrasting
confidence: 78%
“…We forced age and race/ethnicity into the multivariate models as these have been consistently associated with engagement in HIV care in previous studies. 6,17,[22][23][24][25] All analyses were conducted using SAS statistical software (SAS 9.2, SAS Institute, Inc., Cary, NC).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-associated laboratory tests that are reported to public health surveillance have been used as a proxy measure of care engagement of HIV? individuals [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, despite growing interest in the use of HIV surveillance data for measuring care-related outcomes among PLWH at both the national and local levels, there has been only limited comprehensive evaluation of the validity of surveillance data for such purposes. 4,[8][9][10] To date, most nationally representative estimates for HIV-related care measures have validated data from cohort studies against clinical data on HIV care visits. 11,12 In addition, several studies have raised concerns about the accuracy of laboratory data in reflecting linkage to care.…”
Section: Introductionmentioning
confidence: 99%